#MbokodoLeadUs: the gendered politics of black womxn leading campus-based activism in South Africa's recent university student movements. Issue 1 (2nd January 2022) - Mahali, Alude; Matete, Noxolo
ABSTRACT: South Africa has a patriarchal tendency to treat womxn as beneficiaries of protest and activism rather than as agents in the construction of a new socio-political order and as drivers of change through protest. This paper examines the internal gender tensions within South Africa's 2015-2016 student movements including how these tensions materialised publicly; in a sample of university campuses and in the media. The complex particularities of young black womxn who are agitating for an intersectional approach to protest - one that privileges gender - and an end to patriarchy and misogynoir in these movements is observed. Content analysis of self-articulated goals, mission statements on various media and case studies are detailed where black womxn activists constitute majority membership in movements even as they remain disenfranchised in their operationalising. To counter marginality, black womxn student activists' interventions demonstrate a new radical political autonomy that embraces an inclusive feminist ideology.